Students' Discipline Behavior from The Ethics of Learning in The Class - Izza, Faradillah Nurul; Rizaldi, Dedi Riyan; Fahrurrozi, Muhammad; Nilwan, Nilwan; Zaini, Muhamad (Journal of Psychological Perspective, 2022)
This study aims to determine the student's disciplinary behavior seen from the ethics of learning in the classroom. The subjects in this study were 26 students at MA Plus Nurul Islam Sekarbela who showed deviations in discipline. The method used is descriptive qualitative research with a phenomenological approach with the consideration that this study seeks to describe the phenomenon of student discipline behavior. The results of the observations show that the student's discipline as seen from the ethics of learning in the classroom as a whole is good. Although there are still some challenges faced by teachers in enforcing learning discipline to students.